Narkomfin’s new life. A ‘prosthesis’ for Ginzburg and Milinis’s masterpiece - Luca Lanini; Giorgia Puccinelli (Agathón)
The article’s object is to recover the original purpose of the Narkomfin through a satellite architecture that embraces some of the functions no longer in use in the famous building by Ginzburg and Milinis, thus renewing its role as a ‘social condenser’ in contemporary post-Soviet Moscow. The strategy here presented is also a possible ‘good practice’ for the maintenance/modification/reuse of similar complexes, very common in the former Soviet Bloc countries as in the Western post-war social housing heritage, through an advanced tool for housing support.